Analisis Kepuasan Pasien Terhadap Sistem Pendaftaran Rawat Jalan Online di RSUP Dr. Sardjito Yogyakarta - Prajna Pramitha Purba (Jurnal Infokes, 2022)
Anjungan Pendaftaran Mandiri (APM) is an online-based registration system for outpatient at Dr.Sardjito hospital Yogyakarta, reservation for outpatient can be made at least 30 days before the check-up day or a maximum of one day before the check-up day. Although the implementation of the APM system helps patients a lot, there are still many lack from system that felt bt users. The aim of this study was to analyze the patient satisfaction of the APM system users. The method used to measure satisfaction was End User Computing Satisfaction (EUCS) with 5 measurement dimentions (content, accurancy, format, timeliness, and ease of use). The results of the overall mean on 5 dimentions show 2,41 with dissatisfied interpretation, these results also are supported by the interviews conducted on respondents showing that there are still many features and performances of the APM system that need to be improved.